Análise do comportamento mecânico e elaboração de placas sanduíches anisotrópicas - Cunha, Jesiel (1992)
A theoretical and numerical tridimensional .calculation of displacements, strains and stresses in antisymmetric sandwich Plates is presented. The study was carried out in plates, under static bending loads and subjected to hygrothermal actions using the higher-order theory. The developed computational programs use the analytical method with Fourier series and finite element technique.The rupture criterion that best fits the sandwich Plates was also studied. The experimental results demonstrated the efficiency of the implemented models. In a second part of the work, a new type (in Brazil) of support for printed Circuit boards was elaborated with the sandwich paneis conception. The obtained prototype presented good properties, considering the standard of electrical. laminates, with some advantages in relation to its similars.